2010
DOI: 10.1002/bit.22664
|View full text |Cite
|
Sign up to set email alerts
|

Novel micro‐bioreactor high throughput technology for cell culture process development: Reproducibility and scalability assessment of fed‐batch CHO cultures

Abstract: With increasing timeline pressures to get therapeutic and vaccine candidates into the clinic, resource intensive approaches such as the use of shake flasks and bench-top bioreactors may limit the design space for experimentation to yield highly productive processes. The need to conduct large numbers of experiments has resulted in the use of miniaturized high-throughput (HT) technology for process development. One such high-throughput system is the SimCell platform, a robotically driven, cell culture bioreactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 21 publications
1
69
0
Order By: Relevance
“…The typical cell inoculation density was 3.0 -5.0 × 10 5 cells/mL and the culture was routinely passaged three times per week. For MAb3 cell line the cultures were maintained and propagated as described in [9].…”
Section: Media Cell Lines and Culture Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical cell inoculation density was 3.0 -5.0 × 10 5 cells/mL and the culture was routinely passaged three times per week. For MAb3 cell line the cultures were maintained and propagated as described in [9].…”
Section: Media Cell Lines and Culture Propagationmentioning
confidence: 99%
“…Recent literature have demonstrated availability of various designs of micro-scale reactors from a simpler standard plate with integrated sensors called Microtiter plate based bioreactors (MTB) [6][7][8][9][10][11][12] to more advanced cell culture systems such as the Stirred Mini Bioreactors (MBR) with control capabilities close to bench-top bioreactors for high throughput cell culture screening and optimization studies [13][14][15][16][17]. MBRs possess the advantage of being able to closely mirror the bench-scale bio-reactors in their monitoring and control capabilities and hence are considered as a preferred alternative vessel over shake flasks or MTBs for early stage process development.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to cell-line engineering, opting for media optimization considerably reduces development timelines and the complexity of product quality comparability considerations, which typically results from redevelopment of cell lines. High-throughput cell culture systems opened the door for testing many conditions simultaneously [266][267][268] . The technology developed for media optimization in 96-deepwell plates (96-DWP) fed-batch cultures 26,27,251 can also be applied for product quality modulation 25,64 .…”
Section: Introductionmentioning
confidence: 99%
“…Such systems can drastically decrease the time requirement and labor intensity on the sampling actions of mL-scale systems. Advanced online cell culture monitoring technologies are available, including online dielectric spectroscopy 246 and light scattering 191 , which can be used to measure viable cell density and viable cell volume, and online Raman spectroscopy 247 and infrared spectroscopy 248 , which can be used to monitor several culture metabolites and glycoprotein titer. Integration of these technologies into mL-scale bioreactors can reduce the liquid handling activities, solve the problem related to the small sample volume, and more importantly, increase the data throughput and resolution.…”
Section: Scale-down Verificationmentioning
confidence: 99%
“…The mL-scale systems were originally designed for quick screening of clones, media, and culture parameters such as pH and temperature. In recent years, many studies 165,172,190,191 have shown that these mL-scale systems are quite representative for the bioreactors ranging from L-scale to kL-scale.…”
Section: Introductionmentioning
confidence: 99%